2006
DOI: 10.1111/j.1365-2966.2006.10961.x
|View full text |Cite
|
Sign up to set email alerts
|

The SCUBA Half-Degree Extragalactic Survey - II. Submillimetre maps, catalogue and number counts

Abstract: We present maps, source catalogue and number counts of the largest, most complete and unbiased extragalactic submillimetre survey: the 850‐μm SCUBA Half‐Degree Extragalactic Survey (SHADES). Using the Submillimetre Common‐User Bolometer Array (SCUBA) on the James Clerk Maxwell Telescope (JCMT), SHADES mapped two separate regions of sky: the Subaru/XMM–Newton Deep Field (SXDF) and the Lockman Hole East (LH). Encompassing 93 per cent of the overall acquired data (i.e. data taken up to 2004 February 1), these SCU… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
349
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 387 publications
(364 citation statements)
references
References 78 publications
15
349
0
Order By: Relevance
“…Thus, in a statistical ensemble of sources, the same observed flux arises more often from one of many fainter sources than from the few brighter ones, relative to the measured value. We assume a measurement with Gaussian noise (validated by the closely Gaussian jackknife noise distribution) and a 2 mm source count model scaled from observationally constrained 850 μm counts (e.g., Coppin et al 2006;Weiß et al 2009…”
Section: Deboostingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in a statistical ensemble of sources, the same observed flux arises more often from one of many fainter sources than from the few brighter ones, relative to the measured value. We assume a measurement with Gaussian noise (validated by the closely Gaussian jackknife noise distribution) and a 2 mm source count model scaled from observationally constrained 850 μm counts (e.g., Coppin et al 2006;Weiß et al 2009…”
Section: Deboostingmentioning
confidence: 99%
“…For deboosting we followed a Bayesian recipe, such as described in Coppin et al (2005Coppin et al ( , 2006:…”
Section: Deboostingmentioning
confidence: 99%
“…These relatively bright SMGs, which have a median redshift of z∼2.3 and SFR  100 M e yr −1 (Chapman et al 2005), have traditionally been found using bolometer cameras, such as the Submmillimetre Common-User Bolometer Array (SCUBAHolland et al 1999), mounted on single-dish telescopes, such as the 15 m James Clerk Maxwell Telescope (e.g., Coppin et al 2006;Weiß et al 2009b;Wardlow et al 2011;Casey et al 2013;Geach et al 2013). One of the main advantages of single-dish observations is that they can survey sufficiently wide areas of the sky to enable the detection of relatively large numbers of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Results in Figure 7 were derived from observation data taken by instruments with the same angular resolution (i.e., SCUBA and SCUBA-2). Coppin et al (2006) and Casey et al (2013) estimated number counts down to 2 mJy using sources in blank-field. The limitation of faint end flux density is related to the confusion limit.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…• 00 ′ 00 ′′ ) is one of two regions in SHADES where number count (Coppin et al 2006), redshift distribution (Aretxaga et al 2007;Ivison et al 2007;Clements et al 2008) and physical parameters of SMGs (Clements et al 2008) were investigated. In this study, we also investigate number count and physical properties of SMGs in blank-field using 850 µm imaging data centered at (α 2000 , δ 2000 ) = (02 h 18 m 07 s , -04…”
Section: Corresponding Author: H Seomentioning
confidence: 99%